PERANAN KOPERASI BERBASIS AGRIBISNIS DALAM PERTUMBUHAN EKONOMI DI KOTA METRO - Zulkarnain Zulkarnain (STIPER Dharma Wacana Metro, 2014)
The study aims to identify Cooperatives in Metro, Studying patterns of development of agri-based cooperatives in Metro City, knowing cooperating opportunities with national companies, local companies and banking and other business entities that are in Metro City and the surrounding area, and knowing increase growth rate economy achieved with the participation of cooperatives based agribusiness. The result showed that different types of cooperatives to grow and thrive in Metro City, the pattern of development of agribusiness cooperatives in Metro City Through the efforts of the development of agri-commodities terpaudu that will generate profits in the year to 5. The role of the agricultural sector to GDP in Metro City by 11%. This figure reflects that the agricultural sector is still one important sector in driving the economy in Metro City. While the financial and service sector amounted to 22,29%. If the two sector combined, namely agricultural and financial-services then reached 33,29% more. It means that the agricultural sector which is a producer of primary goods and supported by finance and service sector will be able to play an important role in the economy in the City of Metro.Keywords: Cooperatives, development of agri-based, Metro City